INTERAKSI ANTARA Trichoderma harzianum, Penicillium sp. DAN Pseudomonas sp. SERTA KAPASITAS ANTAGONISMENYA TERHADAP Phytophthora capsicilN VITRO - Nandang Suharna (BERITA BIOLOGI, 2003)
A preliminary study has been done to know antagonism capacities of three isolates of Trichoderma harzianum, two isolates of Penicillium sp.and one isolate of Pseudomonas sp.against Phytophthora capsici in vitro and interaction among those six antagonists.The highest antagonism capacity possessed by Penicillium sp. KN1, respectively followed by Penicillium sp.KN2,Pseudomonas sp. GH1 and the three T. harzianum isolates. Except for those three T. harzianum isolates, the two Penicillium sp.isolates and Pseudomonas sp. GH1 isolate indicated anti fungal activity against this fungal pathogen.Based on microscopic observation, there was no mycoparasitism within three T.harzianum isolates against Ph. capsici.While interaction occurred among antagonist showed that Pseudomonas sp.GH1 was antagonistic against the other five antagonists.Growth inhibition by Penicillium sp. KN2 showed against this plant pathogen.Beside the need of further study in green house and field, this result appears the need of study to clarify and identify of the chemical subtance of anti fungal possessed by Penicillium sp. KN1 dan Penicillium sp. KN2.The result showed that the six microbes most potential for biological control agents against Ph. capsici.